The Detection of the parasite Cryptosporidium sp. in Lissachatina fulica snails at the provinces of Guayas and Los Ríos, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2015)
The presence of the parasite Cryptosporidium sp. was detected in snail feces of Lissachatina fulica through staining techniques, in the provinces Guayas and Los Ríos, in coastal Ecuador. The number of samples was determined by a random collection method conducted on alternate days during the rainy season. About 411 live specimens were placed in containers to obtain the fecal material. Subsequently, the detection and identification were performed through a parasitic stool analysis; Ziehl Neelsen modified Safranin–methylene blue and Giemsa techniques were applied. Of all Giant African land snails collected in the provinces Guayas and Los Rios, 48.2% of samples tested positive for Cryptosporidium sp. using the modified Ziehl Neelsen, 17.8% for Giemsa and 14.1% for Safranin–methylene blue techniques. With regards to the evaluation of staining techniques the results were statistically analyzed using ANOVA, there is a significant difference (p
Keywords: Cryptosporidium; Lissachatina fulica; staining techniques; terrestrial gastropod